Analytical modeling of coil inductance in wireless power transfer systems under misalignment conditions - Chen, Zidong (Nanyang Technological University, 2023)
Resonant coils are the most critical energy transfer components of wireless power transfer systems (WPTSs) for Electric Vehicles (EVs). The power transfer efficiency of WPTSs will be optimized when two resonant coils are perfectly aligned. However, the misalignments between two resonant coils are inevitable in practical applications. Poor misalignment will cause high power losses and harmful electromagnetic leakage, which restrict the practicability and safety of WPTSs for EVs. In this paper an accurate analytical model of the inductance of resonant coils is developed, which takes both the case of perfect alignment and the case of horizontal misalignments into consideration. A simulation model based on finite element method tools and a laboratory prototype of the target resonant coils were built to verify the mathematical model. The calculated results based on the analytical model presented in this dissertation are in high agreement with the simulation results and the measured values.